The factors affecting velocity at OBLA in well-trained competitive swimmers - Shimoyama, Y.; Kojima, K.; Ichikawa, H.; Nomura, T. (Biomechanics and Medicine in Swimming X, 2006)
This study was intended to investigate the factors affecting velocity at OBLA (V@OBLA) in well-trained male College swimmers. Continuous progressive swimming was evaluated at three times (pre-test, mid-test and post-test) to measure V02max and an intermittent progressive swimming for measuring V@OBLA and stroke length at various velocities. The subjects carried out endurance training for 6 weeks during those tests. The VO2max and V@OBLA values at mid-test and post-test were significantly higher (p < 0.05) than those at pre-test. No significant differences in SL@ OBLA were apparent among the three tests. Rates of VO2max change correlated significantly (p < 0.05); the rate of SL@OBLA change was not significantly correlated with the rate of V@OBLA change. Increasing V@OBLA in this study might be caused not by stroke efficiency improvement but almost entirely by improved aerobic capacity.